UPAYA MENDORONG PARTISIPASI REMAJA DALAM PEMELIHARAAN KEBERSIHAN LINGKUNGAN SUMBER AIR PADA KOMUNITAS PEMULUNG AL BAHAR DEPOK - Elis Anisah Fitriah (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2013)
This action research aimed to increase trust of the members of Al Bahar community towards the well water so it could reduce the community’s dependences toward clean water supplies from outside. This program has been executed by using participation techniques and empowerment for approximately 2 (two) months with the active involvement of 15 (fifteen) adolescents by increasing their active participation in investigating the problem as well as looking after the environmental sanitation surrounding the wells. The program evaluation of this intervention has showed some significant indications for changes among the members namely awareness of their responsibilities as the user of the wells, reveal their willingness willingness to take care of the environmental sanitation in the area; coming up with ideas to solve some contextual environmental problems.